PADI4 Haplotypes in Association with RA Mexican Patients, a New Prospect for Antigen Modulation - Zavala-Cerna, Maria Guadalupe; Gonzalez-Montoya, Norma Guadalupe; Nava, Arnulfo; Gamez-Nava, Jorge I.; Moran-Moguel, Maria Cristina; Rosales-Gomez, Roberto Carlos; Gutierrez-Rubio, Susan Andrea; Sanchez-Corona, Jose; Gonzalez-Lopez, Laura; Davalos-Rodriguez, Ingrid Patricia; Salazar-Paramo, Mario (Clinical and Developmental Immunology, 2013)
Peptidyl arginine deiminase IV (PAD 4) is the responsible enzyme for a posttranslational modification called citrullination, originating the antigenic determinant recognized by anti-cyclic citrullinated peptide antibodies (ACPA). Four SNPs (single nucleotide polymorphisms) have been described in PADI4 gene to form a susceptibility haplotype for rheumatoid arthritis (RA); nevertheless, results in association studies appear contradictory in different populations. The aim of the study was to analyze if the presence of three SNPs in PADI4 gene susceptibility haplotype (GTG) is associated with ACPA positivity in patients with RA. This was a cross-sectional study that included 86 RA patients and 98 healthy controls. Polymorphisms PADI4_89, PADI4_90, and PADI4_92 in the PADI4 gene were genotyped. The susceptibility haplotype (GTG) was more frequent in RA patients; interestingly, we found a new haplotype associated with RA with a higher frequency (GTC). There were no associations between polymorphisms and high scores in Spanish HAQ-DI and DAS-28, but we did find an association between RARBIS index and PADI4_89, PADI4_90 polymorphisms. We could not confirm an association between susceptibility haplotype presence and ACPA positivity. Further evidence about proteomic expression of this gene will determine its participation in antigenic generation and autoimmunity.